Integrasi Konsep Filsafat Pendidikan Modern Terhadap Pengembangan Pendidikan Agama Islam - M. Multazami; Putri Aurelia Rahmadhoni (PT. AKSARA AKADEMIA INDONESIA, 2025)
The integration of modern educational philosophy is an urgent need in the development of Islamic Religious Education (PAI) to maintain its relevance to the dynamics of the contemporary era characterized by technological advances, social change, and the complexity of student needs. This study aims to analyze key concepts of modern educational philosophy such as progressivism, essentialism, perennialism, and reconstructionism and examine their relevance and contribution to strengthening the paradigm and practice of PAI. This study uses a qualitative approach with a literature study method, involving the analysis of scientific journals, books, and academic documents related to the theme of the integration of educational philosophy and Islamic education. The results of the study indicate that each school of modern educational philosophy has the potential to contribute complementaryly to the development of PAI. Progressivism and reconstructionism provide the basis for active, critical, contextual learning, and responsive to social challenges. Meanwhile, essentialism and perennialism emphasize the importance of core values, universal wisdom, and moral-spiritual foundations that align with the basic principles of Islamic education. The integration of these values ​​can be implemented through the development of a holistic curriculum, dialogic and applicable learning methods, and evaluation that encompasses cognitive, affective, moral, and social aspects. The findings of this study confirm that the integration of modern educational philosophy not only meets academic needs but also serves as a crucial strategy for strengthening the quality and relevance of Islamic Religious Education in the modern era. With this integrative approach, Islamic Religious Education has the potential to shape students who not only understand religious teachings textually but also possess the intellectual, spiritual, and social capacities that support a harmonious, adaptive life and contribute positively to a constantly evolving society. Keywords: Modern Educational Philosophy, Islamic Religious Education, Curriculum Integration